2007
DOI: 10.1002/chin.200712214
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and DNA Topoisomerase‐II Inhibitory Activity of Unnatural Nucleosides.

Abstract: Nucleic acids U 0700Synthesis and DNA Topoisomerase-II Inhibitory Activity of Unnatural Nucleosides. -Among the nucleosides (I) (21 examples) synthesized, only compound (Ic) shows moderate topoisomerase-II inhibitory activity. -(MISHRA, R. C.; DWIVEDI, N.; TRIPATHI*, R. P.; BANSAL, I.; SAXENA, J. K.; Nucleosides, Nucleotides Nucleic Acids 24 (2005) 1, 15-35; Div. Med. Process Chem., Cent. Drug Res. Inst., Lucknow 226 001, India; Eng.) -R. Staver 12-214

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The results of the enzyme inhibitory activity showed that only one of the compounds was active against the DNA-topo-II. Some of the unnatural nucleosides were found to cause degradation or cleavage of DNA in treated cells which indicated that they were acting as antineoplastic agents [101].…”
Section: Carbohydrate Derivatives As Antiparasitic Agentsmentioning
confidence: 99%
“…The results of the enzyme inhibitory activity showed that only one of the compounds was active against the DNA-topo-II. Some of the unnatural nucleosides were found to cause degradation or cleavage of DNA in treated cells which indicated that they were acting as antineoplastic agents [101].…”
Section: Carbohydrate Derivatives As Antiparasitic Agentsmentioning
confidence: 99%
“…Growing this plant will certainly have the positive impacts on the environment, nutrition, and health. Consumption of it protects against diarrhoea, heart disease, eye disease, and a number of other illnesses [4]. Moringa leaves also possess the positive effect against inflammation, spasm, hypertension, tumour, ulcer, epilepsy, diabetes and hepato-proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous molecular targets are known for filarial parasites and few of them have been utilized as potent chemotherapeutic target (Mishra et al, 2005;Muller et al, 1988;Nagarajan et al, 1988;Singh et al, 2007;Singh et al, 2008). DNA topoisomerases are involved in managing the topological problems associated with DNA replication, transcription, recombination and chromatin remodeling by introducing temporary single or double stranded breaks in the DNA.…”
Section: Introductionmentioning
confidence: 99%